Safety and Efficacy of Chimeric Yellow Fever-Dengue Virus Tetravalent Vaccine Formulations in Nonhuman Primates - Guirakhoo, F. (American Society for Microbiology, 2004)
To construct chimeric YF/DEN viruses (ChimeriVax-DEN), the premembrane (prM) and envelope (E) genes of yellow fever (YF) 17D virus were replaced with those of each wild-type (WT) dengue (DEN) virus representing serotypes 1 to 4. ChimeriVax-DEN1-4 vaccine viruses were prepared by electroporation of Vero cells with RNA transcripts prepared from viral cDNA (F. Guirakhoo, J. Arroyo, K. V. Pugachev, C. Miller, Z.-X. Zhang, R. Weltzin, K. Georgakopoulos, J. Catalan, S. Ocran, K. Soike, M. Ratteree, and T. P. Monath, J. Virol. 75:7290-7304, 2001; F. Guirakhoo, K. Pugachev, J. Arroyo, C. Miller, Z.-X. Zhang, R. Weltzin, K. Georgakopoulos, J. Catalan, S. Ocran, K. Draper, and T. P. Monath, Virology 298:146-159, 2002). Progeny viruses were subjected to three rounds of plaque purifications to produce the Pre-Master Seed viruses at passage 7 (P7). Three further passages were carried out using U.S. current Good Manufacturing Practices (cGMP) to produce the Vaccine Lot (P10) viruses. Preclinical studies demonstrated that the vaccine candidates are replication competent and genetically stable and do not become more neurovirulent upon 20 passages in Vero cells. The safety of a tetravalent vaccine was determined and compared to that of YF-VAX in a formal monkey neurovirulence test. Brain lesions produced by the tetravalent ChimeriVax-DEN vaccine were significantly less severe than those observed with YF-VAX. The immunogenicity and protective efficacy of four different tetravalent formulations were evaluated in cynomolgus monkeys following a single-dose subcutaneous vaccination followed by a virulent virus challenge 6 months later. All monkeys developed low levels of viremia postimmunization, and all the monkeys that had received equal concentrations of either a high-dose (5,5,5,5) or a low-dose (3,3,3,3) formulation seroconverted against all four DEN virus serotypes. Twenty-two (92%) of 24 monkeys were protected as determined by lack of viremia post-challenge. This report is the first to demonstrate the safety of a recombinant DEN virus tetravalent vaccine in a formal neurovirulence test, as well as its protective efficacy in a monkey challenge model.